Northwest History. Alaska, Glaciers. United States. (1937)
Hotel In Path Of Alaska Glacier. ALASKA GLACIER FAIRBANKS, Alaska, Feb. 11.—(/P)—Black Rapids glacier, once considered "dying," rumbled and boomed today in its march toward a hostelry where a worried family poised for flight. The glacier buckled in the middle of its 30-mile length as though gathering itself for a drive down a mile and a half of moraine toward Rapids roadhouse, occupied by Mr. and Mrs. H. E. Revell and their son, Harry. Antics of the glacier, which began advancing this winter after receding for several years, drew the attention of scientists at the University of Alaska. Otto Geist, in charge of the university's museum, flew to the glacier 125 miles south of here and near the Richardson highway, in an attempt to learn what caused the ice to misbehave. Aviators discussed the practicability of dropping bombs to break the glacier's "back." The idea-rleveloped no further than this. Immense blocks of ice crashed off the 200-foot high and two-mile wide face of the glacier in a temperature of 10 degrees below zero. Some observers attributed the renewed activity of the glacier to a recent earthquake.